Exogenous dissolved organic matter redirects humic carbon fate at mineral interfaces through pre-contact molecular conditioning - Yu Li; Guangxu Mi; Jianghao Cheng; Meiling Zhang; Ying Liu; Shuang Ai; Fan Yang; Kui Cheng (Water Research, 2026)

Artificial humic acid reshapes microbial C-N metabolism and nitrogen partition in microplastic-contaminated soils - Qihe Gao; Shuang Ai; Meiling Zhang; Yu Li; Yantong Li; Yadong Ma; Jiale Zhang; Fan Yang; Kui Cheng (Journal of Hazardous Materials, 2026)

Experimental study on the bearing performance of high pile cap foundation under the coupling effect of scouring and horizontal cyclic loads - Lunliang Duan; Linghao Zhang; Pei Yuan; Yankun Zhang; Duoyin Wang; Meiling Fan; Bo Geng (Soil Dynamics and Earthquake Engineering, 2026)

Linking molecular heterogeneity of artificial humic acid to divergent cadmium coordination behaviors - Yu Li; Xianghui Meng; Shuang Ai; Meiling Zhang; Guangxu Mi; Yurun Miao; Zhuqing Liu; Fan Yang; Kui Cheng (Journal of Hazardous Materials, 2026)

Bioinspired domed cone-pillar nanoarrays design for robust and low-haze-transparent superhydrophobic quartz glass - Yingying Dou; Yue Fan; Qiongwen Fu; Meiling Tao; Junyin Ouyang; Hongtao Liu; Lin Liu; Yabin Yang; Shilin Huang; Shan Zhou; Xuelin Tian (Chemical Engineering Journal, 2026)

Synergistic atomic-level anchoring and pore engineering of cobalt-nitrogen-carbon for anti-fouling and robust capacitive deionization - Huakun Pan; Haodong Zhang; Xinxi Teng; Yang Fan; Yaming Wang; Lin Li; Guisong Zhang; Meiling Liu; Haiou Song; Aimin Li; Shupeng Zhang (Chemical Engineering Journal, 2026)

SEMA4A promotes acute myeloid leukemia progression through inhibiting apoptosis - Xinyu Li; Binyu Yao; Meiling Sun; Wangshi Li; Xingzhi Lv; Keyang Luo; Yue Wu; Ruolin Xiu; Yuzhu Ma; Fukai Liu; Yanhong Zhao; Shengjin Fan; et al. (Genes & Genomics, 2026)

Spatiotemporal Profiling of Intratumoral Free Payload Distribution via MALDI Imaging Mass Spectrometry: Implications for Drug-to-Antibody Ratio Optimization in Antibody–Drug Conjugates - Tingting Cai; Ziyi Li; Qiaofang Yan; Guangcun Huang; Kaiying Jia; Xiaotong Chen; Junling Dun; Jinghua Zou; Meiling Tan; Yue Wu; Fan Wang (The AAPS Journal, 2026)

Enhanced electrocatalytic degradation of concentrated simulated metronidazole wastewater by MIL-101(FeCu)/graphite felt electrodes - Songshan Jiang; Fan Wu; Rui Wen; Lin Xu; Qian Zhong; Meiling Yang; Bai He; Huan Yi; Huan Pang (Chemical Engineering Journal, 2026)

Bibliometric analysis of Pseudomonas aeruginosa vaccine development highlighting research status, evolution, and future opportunities - Shiqin Huang; Yi Zhou; Meiling Wu; Xinyan He; Jie Liu; Xinyao Chen; Chunyong Xia; Wen Wu; Ying Fan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

The changes of antioxidant system, membrane integrity and phenolics metabolism participate in bongkrekic acid and adenosine triphosphate-mediated energy status regulating longan pericarp browning - Meiling Li; Hetong Lin; Ruiling Zhuo; Boqiang Li; Yifen Lin; Yihui Chen; Zhongqi Fan; Hui Wang (Postharvest Biology and Technology, 2026)

Comparative assessment of female reproductive toxicity from PFOA and its alternative GenX in mice and human granulosa cells - Yangyang Yuan; Binhui Wang; Yuyu Fan; Meiling Le; Lihai Wu; Shiyi Deng; Jian Huang; Dalei Zhang (Toxicology and Applied Pharmacology, 2026)

Visible light driven highly selective oxidation of HMF coupled with H2 evolution via bimetal-doped synergism on ZnIn2S4 nanosheets - Yachen Hu; Wei Jiang; Zijun Zhang; Qinqin Jiang; Yawen Jiang; Lang Sun; Panjing Xu; Yanling Chang; Chuanqiang Wu; Ziming Fan; Meiling Wang; Zhou Chen; et al. (Chemical Engineering Journal, 2025)

AKR1B1 is Required for Maintaining Acute Leukemia Cell Survival by Epigenetic Silencing of Tumor Suppressor Genes - Jingyu Chen; Lu Xu; Wangshi Li; Meiling Sun; Yao Chen; Ting Qiu; Yue Wu; Xingzhi Lv; Fukai Liu; Huitao Fan (Biochemical Genetics, 2025)

The intergrowth of YTa7O19 in L-Ta2O5 with Er3+/Yb3+ enhancing pure green upconversion luminescence intensity by molten salt synthesis - Yuhan Fan; Yongze Cao; Zhihua Zhang; Hualong Tao; Meiling Li; Xizhen Zhang; Sai Xu; Baojiu Chen (Chemical Engineering Journal, 2025)

Comparative transcriptomic and metabolomic analyses reveal the role of acidic electrolyzed-oxidizing water in enhancing disease resistance in Phomopsis longanae Chi-infected longans - Meiling Li; Zhongqi Fan; Xiaoze Dai; Mengshi Lin; Yifen Lin; Hui Wang; Ruiling Zhuo; Yen-Con Hung; Hetong Lin; Yihui Chen (Postharvest Biology and Technology, 2025)

Three birds with one stone: a facile superparamagnetic aptasensor for selective capture, dual-mode detection and efficient elimination of methicillin-resistant Staphylococcus aureus - Fengfeng Zhao; Yuming Yao; Shuo Ma; Jiwei Wang; Abudushalamu GuliNaizhaer; Meiling Zhou; Yaya Chen; Xun Gao; Xiaobo Fan; Chen Zhang; Xinglu Jiang; Guoqiu Wu (Chemical Engineering Journal, 2025)

Spatiotemporal impacts of scientific and technological innovation and industry chain resilience on ecological Efficiency: Evidence from 284 Chinese cities - Meiling Wu; Wei Liu; Rongguang Zhang; Zhiran Fan; Xueyan Zhong (Journal of Environmental Management, 2025)

Altering wilting time and chopping length to optimize Medicago polymorpha L. fermentation ripening rate and flavour - Ning Mao; Hanyu Zhang; Ermei Du; Meiling Fan; Shihao Liu; Chaosheng Liao; Chao Chen; Hong Sun; Yulong Zheng; Ping Li; Yixiao Xie (Food Bioscience, 2025)

Multi-residue analytical method development and dietary exposure risk assessment of 345 pesticides in mango by LC-Q-TOF/MS - Xingqiang Wu; Jianxun Li; Jing Wei; Kaixuan Tong; Yujie Xie; Qiaoying Chang; Xiaoxuan Yu; Bei Li; Meiling Lu; Chunlin Fan; Hui Chen (Food Control, 2025)

Deep Learning Imaging-Based Reconstruction Improved the Image Quality of Synthetic High B-Value DWI for Prostate Lesion Detecting - Xiuxiu Zhou; Hanxiao Zhang; Song Jiang; Jiankun Dai; Lingling Gu; Pei Zhang; Ye Fu; Jie Shi; Xinyi Wan; Meiling Xu; Shiyuan Liu; Li Fan (Journal of Medical and Biological Engineering, 2025)

Acrylamide drives amidase-mediated gut dysbiosis to aggravate colitis - Daotong Li; Yinghua Luo; Huimin Fan; Li Dong; Xiaoying Zhang; Yu Feng; Meiling Tian; Shuqing Zhang; Wenjing Chen; Lujia Zhang; Jianwei Gao; Xiangning Ma; et al. (Science Bulletin, 2025)

2D manganese-doped calcium carbonate nanosheets as activable MRI/US imaging Guided enhanced calcium influx for Boosted regulatory cell death - Mingya Tan; Linlin Huo; Jie Zeng; Shiqi Zhu; Jianfeng Bao; Mengke Fan; Jiangyang Li; Meiling Liu; Jiayi Zhao; Zhenghuan Zhao (Chemical Engineering Journal, 2025)

Dynamic planning of crowd evacuation path for metro station based on Dynamic Avoid Smoke A-Star algorithm - Songtao Zuo; Zhanli Mao; Chuangang Fan; Xin Chen; Meiling Gong; Jianxing Ren; Xiaoxiao Fan; Yongnan Guo (Tunnelling and Underground Space Technology, 2024)

Synergistic enhancement of cadmium immobilization and soil fertility through biochar and artificial humic acid-assisted microbial-induced calcium carbonate precipitation - Yu Li; Meiling Zhang; Xiaobin Wang; Shuang Ai; Xianghui Meng; Zhuqing Liu; Fan Yang; Kui Cheng (Journal of Hazardous Materials, 2024)

Three nona-2,7-dienoic acid derivatives from saltern derived Micromonospora sp. FXY415 - Meiling Wang; Zhonghui Zheng; Zhiyu Hu; Binbin Fan; Jiexi Liu; Qingyan Xu (Natural Product Research, 2024)

Dynamic response of sloping seabed with buried twin pipelines under wave loading - Fan Meiling; Duan Lunliang; Zhou Jianting; Liu Zhuang; Wang Duoyin (Ocean Engineering, 2024)

Acidic electrolyzed-oxidizing water treatment mitigated the disease progression in Phomopsis longanae Chi-infected longans by modulating ROS and membrane lipid metabolism - Meiling Li; Hetong Lin; Chao Wang; Yazhen Chen; Mengshi Lin; Yen-Con Hung; Yifen Lin; Zhongqi Fan; Hui Wang; Yihui Chen (Food Chemistry, 2024)

Elevated CO2 exacerbates the risk of methylmercury exposure in consuming aquatic products: Evidence from a complex paddy wetland ecosystem - Danni Wu; Lei Chen; Xueying Zong; Fan Jiang; Xiaojie Wang; Meiling Xu; Fuxun Ai; Wenchao Du; Ying Yin; Hongyan Guo (Environmental Pollution, 2024)

Migration and transformation of soil phosphorus by organic acids: a global meta-analysis - Ying Zhao; Meiling Zhang; Zhuqing Liu; Fan Yang (Journal of Soils and Sediments, 2024)

Evolution of sustainability and its driving characteristics in typical energy-rich counties in underdeveloped Northwest China - Honghua Li; Xingang Fan; Meiling Yang; Xueli Chen; Manman Zhao (Environment, Development and Sustainability, 2024)

The role of energy transport system in pericarp browning of harvested longan fruit - Meiling Li; Hetong Lin; Yazhen Chen; Yihui Chen; Yifen Lin; Zhongqi Fan; Hui Wang (Postharvest Biology and Technology, 2024)

Silver nanowire-infused carbon aerogel: A multifunctional nanocellulose-derived material for personal thermal management - Meiling Zhang; Yinan Fan; Ni Wang; Hongguo Gao; Lei Zhang; Yanjiao Zhao; Lifang Liu (Carbohydrate Polymers, 2024)

Progress on the roles of zinc in sperm cryopreservation - Yuanyou Li; Shaoyu Qin; Wenfei Cui; Fan Zhao; Meiling He; Zhongliang Jiang (Theriogenology, 2023)

A halogen-free hyper-crosslinked ionic polymer for efficient multi-conversion of CO2 into carbonates under mild conditions, with a combination of theoretical study - Bowen Jiang; Jia Liu; Wenjie Xiong; Meiling Weng; Jigang An; Yuewei Fan; Leizhi Zheng; Guoqiang Yang; Zhibing Zhang (Chemical Engineering Journal, 2023)

A new S-scheme heterojunction of 1D ZnGa2O4/ZnO nanofiber for efficient photocatalytic degradation of TC-HCl - Wenhui Chen; Tianxin Kang; Fenqi Du; Peipei Han; Meiling Gao; Peng Hu; Feng Teng; Haibo Fan (Environmental Research, 2023)

Numerical study of regular wave-induced oscillatory soil response during the caisson installation - Lunliang Duan; Chenxi Qin; Jianting Zhou; Guangwu Tang; Duoyin Wang; Meiling Fan (Ocean Engineering, 2023)

An injectable antibacterial hydrogel to regulate ocular immune for endophthalmitis treatment - Zunzhen Ming; Lin Han; Huanhuan Zhu; Meiyu Bao; Qiangyuan Fan; Shaobo Xue; Kesheng Wang; Yue Zhang; Meiling Lu; Chongshun Xu; Qi Wu; Tingting Li; et al. (Chemical Engineering Journal, 2023)

Nonconservative behavior of dissolved molybdenum and its potential role in nitrogen cycling in the Bohai and Yellow Seas - Jinqi Fan; Liqin Duan; Meiling Yin; Huamao Yuan; Xuegang Li (Frontiers in Marine Science, 2022)
Molybdenum plays an important role in marine biological activity, especially in nitrogen cycling as a cofactor for N 2 fixation and nitrate reductase. However, the dissolved Mo (dMo) behavior and its interaction with N cycling in the coastal waters is still unclear. In this study, the dMo concentrations and parameters related to Mo distribution and N cycling in surface and bottom seawaters of the Bohai (BS) and Yellow Seas (YS) were examined. The results showed that dMo concentrations ranged from 36.4 nmol L -1 to 125.0 nmol L -1 , most of which deviated significantly from the conservative line, indicating nonconservative behavior of Mo relative to salinity. The highest dMo concentrations occurring in 36°N section of north of the South YS (SYS), were close to conservative value (105 nmol L -1 ). Significant depletion up to 40-50 nmol L -1 of dMo mainly appeared in the BS, NYS and south of the SYS, suggesting the possible removal of dMo by biological utilization and particle adsorption. Particularly, the increasing dMo concentrations away the Yellow River estuary indicated that freshwater dilution was one of reasons for dMo distributions in the BS. The similar spatial distribution of dMo and dissolved Mn concentrations suggested the possible scavenging by MnO x phases for Mo removal. The negative correlation between dMo and chlorophyll- a (Chl- a ) concentrations in surface seawaters suggested that biological uptake was involved in dMo removal. The depleted dMo in most of sites corresponded with the higher nitrite concentrations, implying the possible involvement of nitrate reduction process. Although the highest N 2 fixation rates and relative abundances of cyanobacteria appeared in 36°N section, corresponding with the conservative dMo, suggesting that Mo may play a minor role in N 2 fixation process there. The ten-folds of relative abundance of bacteria with nitrate reduction function than that with N 2 fixation function suggested that dMo seems to play more important role in nitration reduction than nitrogen fixation in the BS and YS.

Implications of spatial priority areas for hydrological ecosystem services through coupling hydrology model and Zonation model under different economic costs of water utilizations in northernmost of Japan - Min Fan; Manjiang Shi; Yunfeng Liu; Wen Chen; Yue Deng; Meiling Wang (Mitigation and Adaptation Strategies for Global Change, 2022)

Exendin-4 Reversed the PC12 Cell Damage Induced by circRNA CDR1as/miR-671/GSK3β Signaling Pathway - Hui Quan; Qiudan Chen; Kesheng Wang; Qinwan Wang; Meiling Lu; Yue Zhang; Sujing Qiang; Shaobo Xue; Lin Han; Huanhuan Zhu; Qiangyuan Fan; Meiyu Bao; et al. (Journal of Molecular Neuroscience, 2021)

Genome-wide investigation of microsatellite polymorphism in coding region of the giant panda (Ailuropoda melanoleuca) genome: a resource for study of phenotype diversity and abnormal traits - Meiling Cheng; Jianying Ren; Fujun Shen; Yan Huang; Zhenxin Fan; Megan Price; Bisong Yue; Xiuyue Zhang (Mammal Research, 2019)

Analysis of ΔpH and the xanthophyll cycle in NPQ of the Antarctic sea ice alga Chlamydomonas sp. ICE-L - Shanli Mou; Xiaowen Zhang; Naihao Ye; Jinlai Miao; Shaona Cao; Dong Xu; Xiao Fan; Meiling An (Extremophiles, 2013)

Long-term cultured callus and the effect factor of high-frequency plantlet regeneration and somatic embryogenesis maintenance in Zoysia japonica - Li Liu; Xiaoli Fan; Junwei Zhang; Meiling Yan; Manzhu Bao (In Vitro Cellular & Developmental Biology - Plant, 2009)